EFFICACY OF TEBUCONAZOLE 25%WG AGAINST BLAST AND SHEATH BLIGHT DISEASES OF RICE IN CENTRAL WESTERN GHATS OF UTTAR KANNADA DISTRICT - GURUDATT M. HEGDE (The Bioscan, 2015)
A new molecule Tebuconazole 25% WG was tried against blast and sheath blight diseases of rice during Kharif 2010-11 and 2011-12 in Paddy Research Station, Malagi. The two years results revealed that, Tebuconazole @0.2% has significantly reduced the blast (17.72%) and sheath blight(10.24%) incidence and correspondingly increased the yields (41.40q/h). The maximum blast (62.07%) and sheath blight (28.16%) was recorded in untreated control plots with lower yields (22.96q/h). Hence, Tebuconazole@ 0.2% can be recommended as an alternate molecule to carbendazim and Tricyclozole for effective management of blast and sheath blight diseases of paddy.